Automatic optical switch. - Abdullah, Mohammad Khazani (2003)

(untitled)
This project is to develop a network switch for protection purposes. The devise, named the Automatic protection Switch (APS) System consist of Coupler Module at the trasmitter side and APS Module at the receiver. APS provides an automated switching between the main and protection fibres (in case of faulty fibres) to support a survivale fibre optic link or network system. It is the perfect add-on solution for the existing fibre optic links or network system equipment without any modification. It is also provide alarms and indicators to warn users of the loss of the main local optical source and faults in the main fibre. Developing the APS will involve the electronics circuits design as well as the optical components integration. ASP consist of switching devices, photodetectors, camparator circuits and fibre components. A small portion of the optical signal from the Main Line is tapped to the comparator circuit. The compactor circuit is the key element which controlc the optical switch, whether to select signals from the Main Line or Protection Line. Since the comparator circuit is working fully in electrical environment, a photodetector is needed is needed to convert the optical signal into the electrical signal prior to the comparator.